Human type I interferons protect Vero E6 and ARPE-19 cells against West Nile virus and are neutralized by pathogenic autoantibodies - Alessandro Ferrari; Irene Cassaniti; Francesca Rovida; Daniele Lilleri; Stefania Croce; Francesca Trespidi; Stefano Ghirardello; Adrian Gervais; Shen-Ying Zhang; Jean-Laurent Casanova; Alessandro Borghesi; Fausto Baldanti (Scientific Reports)
Abstract Auto-antibodies (auto-Abs) that neutralize type I interferons (IFNs) have been implicated in severe viral infections, including ~ 40% of cases of West Nile virus (WNV) neuroinvasive disease (WNND). Developing robust in vitro models to evaluate the protective effects of type I IFNs against viral infection, as well as the disruptive effects of auto-Abs, is essential for understanding disease pathogenesis and identifying patients at risk. In this study, we used Vero E6 and ARPE-19 cell lines to investigate the ability of type I (IFN-α, IFN-β, IFN-ω), type II (IFN-γ), and type III (IFN-λ1) IFNs to restrict WNV infection. Our results demonstrate that IFN-α, IFN-β, and IFN-ω effectively protect ARPE-19 cells from WNV infection, with IFN-β exhibiting the strongest antiviral effect. In contrast, Vero E6 cells required higher concentrations of IFN-ω to achieve comparable protection. Neither IFN-γ nor IFN-λ1 conferred protection in either cell line. We further screened serum samples from WNV-infected patients for auto-Abs neutralizing type I IFNs. Our findings confirm that the ARPE-19-based assay is consistent with other established methods for detecting neutralizing auto-Abs against type I IFNs. This simple and reliable assay offers a valuable tool for assessing the antiviral effects of type I IFNs and the neutralizing activity of auto-Abs in both research and clinical settings. Future studies should aim to validate the clinical utility of the ARPE-19-WNV infection model on a larger scale.